A prodrug-doped cellular Trojan Horse for the potential treatment of prostate cancer. (June 2016) - Levy, Oren; Brennen, W. Nathaniel; Han, Edward; Rosen, David Marc; Musabeyezu, Juliet; Safaee, Helia; Ranganath, Sudhir; Ngai, Jessica; Heinelt, Martina; Milton, Yuka; Wang, Hao; Bhagchandani, Sachin H.; et al.
Abstract: Despite considerable advances in prostate cancer research, there is a major need for a systemic delivery platform that efficiently targets anti-cancer drugs to sites of disseminated prostate cancer while minimizing host toxicity. In this proof-of-principle study, human mesenchymal stem cells (MSCs) were loaded with poly(lactic-co-glycolic acid) (PLGA) microparticles (MPs) that encapsulate the macromolecule G114, a thapsigargin-based prostate specific antigen (PSA)-activated prodrug. G114-particles (∼950 nm in size) were internalized by MSCs, followed by the release of G114 as an intact prodrug from loaded cells. Moreover, G114 released from G114 MP-loaded MSCs selectively induced death of the PSA-secreting PCa cell line, LNCaP. Finally, G114 MP-loaded MSCs inhibited tumor growth when used in proof-of-concept co-inoculation studies with CWR22 PCa xenografts, suggesting that cell-based delivery of G114 did not compromise the potency of this pro-drug in-vitro or in-vivo . This study demonstrates a potentially promising approach to assemble a cell-based drug delivery platform, which inhibits cancer growth in-vivo without the need of genetic engineering. We envision that upon achieving efficient homing of systemically infused MSCs to cancer sites, this MSC-based platform may be developed into an effective, systemic 'Trojan Horse' therapy for targeted delivery of therapeutic agents to sites of metastatic PCa.